Extraction and chemical composition of Tetraclinis articulata (Vahl) mast oil: Oil's value as a natural antioxidant and environmentally benign inhibitor of mild steel corrosion in HCl - Elouadi Yassir; Benhiba Fouad; El Faydy Mohammed; Elmsellem Hicham; Bendaif Hajar; Hafez Baraa; Hachmi Azeddine; Arabi Mourad; Zarrouk Abdelkader (E3S Web of Conferences)
This research aims to address three distinct aspects. Initially, it seeks to extract and characterize the chemical components of Tetraclinis articulata (Vahl) mast leaf oil. Subsequently, it evaluates the oil's antioxidant properties. Lastly, it examines the oil's ability to inhibit mild steel corrosion in 1M HCl through electrochemical methods. The oil's chemical analysis reveals various fatty acids, with 9,12-octadecadienoic acid and methyl ester being the predominant compounds (50.86%). The oil demonstrates a DPPH scavenging ability of 85%, comparable to ascorbic acid's 93%. The corrosion-inhibiting properties of Tetraclinis articulata (Vahl) mast leaf oil on mild steel in a molar acid environment were evaluated through weight loss measurements, electrochemical impedance spectroscopy (EIS), and Tafel polarization curves. The results hint that the oil's effectiveness boosts with concentration, reaching 89.4% at 0.8 g/L. Temperature influences were also scrutinized, and the associated thermodynamic parameters were figured and dissected.